2003
DOI: 10.1071/wr02087
|View full text |Cite
|
Sign up to set email alerts
|

Use of burrows by the endangered pygmy blue-tongue lizard, Tiliqua adelaidensis (Scincidae)

Abstract: The pygmy blue-tongue lizard, Tiliqua adelaidensis, had been considered extinct until its recent rediscovery near Burra in the mid-north of South Australia. The lizards apparently rely on spider burrows with a single entrance as refuge sites. In this paper we describe observations from all-day video recordings of the entrances of burrows occupied by lizards on 31 days across the spring and early summer of 1996. The lizards spent most of each day either retreated down the burrow or basking at the burrow entranc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
70
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 69 publications
(72 citation statements)
references
References 16 publications
2
70
0
Order By: Relevance
“…Tiliqua adelaidensis, the pygmy bluetongue lizard, is within the same lineage of Australian skinks as the Egernia species (Greer 1989;Chapple 2003), but is predominantly solitary (Milne et al 2003). It is now restricted to a few fragments of once more extensive native grasslands near Burra in South Australia, and is categorized as endangered under the Australian Environment Protection and Biodiversity Conservation Act, 1999.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Tiliqua adelaidensis, the pygmy bluetongue lizard, is within the same lineage of Australian skinks as the Egernia species (Greer 1989;Chapple 2003), but is predominantly solitary (Milne et al 2003). It is now restricted to a few fragments of once more extensive native grasslands near Burra in South Australia, and is categorized as endangered under the Australian Environment Protection and Biodiversity Conservation Act, 1999.…”
Section: Introductionmentioning
confidence: 97%
“…Individual lizards occupy narrow vertical burrows, apparently constructed by lycosid and mygalomorph spiders (Hutchinson et al 1994;Fellows et al 2009). The burrows are used for shelter , and as sites to ambush passing invertebrate prey (Milne et al 2003). Lizards prefer the deepest burrows available, and optimal refuges are often in short supply (Souter 2003;Fellows et al 2009).…”
Section: Introductionmentioning
confidence: 99%
“…This lizard species was thought to be extinct after not being seen for over 30 years (ehmann, 1982; hutchinson et al 1994) until they were re-discovered in 1992, after one was found in the stomach of a road killed eastern brown snake (Pseudonaja textilis) (Armstrong & reid, 1992). Since its rediscovery, the pygmy bluetongue lizard has been the focus of a number of studies investigating its behaviour and habitat preferences (milne et al, 2003;Souter, 2006;Fellows et al, 2009;Fenner & Bull, 2010). however, very little is known, either about the other reptile species co-occurring in the same temperate grassland habitat, or about the dynamics of the combined native grassland reptile community.…”
Section: Introductionmentioning
confidence: 99%
“…Subsequent surveys have documented its limited geographical range in a few isolated remnant patches of native grassland in the mid-north region of South Australia, an area that is now extensively fragmented by agricultural activities, and have assessed it to be an endangered species (Milne et al 2003a). Individual lizards are solitary and spend most of their time associated with single entrance, vertical burrows constructed by lycosid and mygalomorph spiders (Milne et al 2003b;Fenner et al 2007;Ebrahimi et al 2012).…”
mentioning
confidence: 99%
“…. Lizards occasionally move out of their burrows to defecate, lunge at passing invertebrate prey, or to seek mating partners for a brief period in the spring, but otherwise are almost entirely confined to their burrows, the burrow entrances and an extremely small area around the burrow entrance (Milne et al, 2003b;Fenner et al, 2007;Fenner and Bull, 2011;Schofield et al, 2012;Ebrahimi et al, 2014). As a consequence, we assume that most of their interspecific interactions also take place around the burrow entrance.…”
mentioning
confidence: 99%